2014
DOI: 10.1371/journal.pone.0083302
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Induced Changes in Attentional Allocation during Categorization: A Sizable Catalog of Attention Change as Measured by Eye Movements

Abstract: Learning how to allocate attention properly is essential for success at many categorization tasks. Advances in our understanding of learned attention are stymied by a chicken-and-egg problem: there are no theoretical accounts of learned attention that predict patterns of eye movements, making data collection difficult to justify, and there are not enough datasets to support the development of a rich theory of learned attention. The present work addresses this by reporting five measures relating to the overt al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“… Blair et al (2009a) concluded that after learning to correctly categorize the microorganisms, participants’ attention distribution improved: over time, more time was spent looking at relevant features compared to the irrelevant feature. This finding was replicated in further studies with the same stimulus materials ( Blair et al, 2009b ; McColeman et al, 2011 ). More broadly, the idea that learners optimize their attention to look more at relevant information and less at irrelevant information with practice is known as the information reduction hypothesis ( Haider and Frensch, 1999 ).…”
Section: Introductionsupporting
confidence: 63%
“… Blair et al (2009a) concluded that after learning to correctly categorize the microorganisms, participants’ attention distribution improved: over time, more time was spent looking at relevant features compared to the irrelevant feature. This finding was replicated in further studies with the same stimulus materials ( Blair et al, 2009b ; McColeman et al, 2011 ). More broadly, the idea that learners optimize their attention to look more at relevant information and less at irrelevant information with practice is known as the information reduction hypothesis ( Haider and Frensch, 1999 ).…”
Section: Introductionsupporting
confidence: 63%
“…Facing these challenges, VCL relies on two fundamental processes. The first process is attentional learning, which enables the volitional allocation of attention to relevant features, while ‘filtering out’ distracting salient features that have little relevance for categorization ( Rehder and Hoffman, 2005 ; Sloutsky and Fisher, 2008 ; Blair et al, 2009 ; Hoffman and Rehder, 2010 ; Sloutsky, 2010 ; McColeman et al, 2014 ). The second process is perceptual learning, which enables becoming more sensitive to subtle, initially hard to detect differences between objects from different categories ( Shiffrin and Schneider, 1977 ; Goldstone, 1994 , 1998 ; Goldstone et al, 2001 ; Roelfsema et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The third characteristic is the number of categories; data sets we selected either have two or four response options. Each of the four previously-published data sets contained choice and eye-tracking data, and were generously made freely available in Mccoleman et al [47]. We next describe the main details of each data set, but refer to Mccoleman et al [47] for additional details.…”
Section: Data Overviewmentioning
confidence: 99%
“…After making a categorization, each of the 33 participants received corrective feedback. For additional details, we refer readers to original articles [47,48].…”
Section: Data Set 1: Two-alternative Rule-basedmentioning
confidence: 99%